2007
DOI: 10.1007/s11274-007-9625-y
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community and decomposition rate in long term fed-batch composting using woodchip and Polyethylene terephthalate (PET) as bulking agents

Abstract: Long term fed-batch composting experiments were conducted for 200 days using two types of bulking agents; woodchip and PET flake, with periodic compost withdrawal through a washing process. The bacterial communities of composting materials in the two different bulking agents were also investigated by 16S rRNA gene clone analysis. The decomposition rate in both composting reactors was 86.1% and 88.2% of the total organic load, respectively. The control experiment of dead-end operation without compost withdrawal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…These results showed a dominance of the order Bacillales (54%) and ''Lactobacillales'' (38%) in the reactor using plastic bottle flakes. On the other hand, the order Bacillales dominant (95%) and ''Lactobacillales'' was not detected from the reactor using woodchips (Nagao et al 2008). The dominance of the order ''Lactobacillales'' might be correlated with the oxygen concentration and temperature in the reactor.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…These results showed a dominance of the order Bacillales (54%) and ''Lactobacillales'' (38%) in the reactor using plastic bottle flakes. On the other hand, the order Bacillales dominant (95%) and ''Lactobacillales'' was not detected from the reactor using woodchips (Nagao et al 2008). The dominance of the order ''Lactobacillales'' might be correlated with the oxygen concentration and temperature in the reactor.…”
Section: Discussionmentioning
confidence: 90%
“…In general, the genus Bacillus is often detected from the composting reactors as the major species (Dees and Ghiorse 2001;Strom 1985a, b;Pedro et al 2001). And there are only a few reports in which the order ''Lactobacillales'' in the composting process is dominant (Ishii et al 2000;Hemmi et al 2004;Nagao et al 2008). Nagao et al (2008) revealed the bacterial communities in the small-scale reactor using woodchips and plastic bottle flakes as bulking agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The serious problem of plastic pollution has generated a wake-up call for searching effective and friendly alternatives for the treatment of plastics with the aim to reduce their impact on the environment, alleviate disposal problems and achieve their sustainability [4], [9]. In recent years, a promising alternative for the solid waste management by composting processes has emerged as an attractive option to the conventional recycling process (such as incineration) which generate toxic compounds released in the air and low heat e ciency due to its high moisture content [10]. The composting strategy can reduce the impact of the plastic at the end of its useful life, mainly when it comes to plastic products which are most likely mismanaged or whose recycling is not feasible, as those used for packaging (PET and PE).…”
Section: Introductionmentioning
confidence: 99%